2022
DOI: 10.1177/17590914211073276
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Polyglycerol Amine: An Enhanced Substrate to Support Long-Term Neural Cell Culture

Abstract: Long-term stable cell culture is a critical tool to better understand cell function. Most adherent cell culture models require a polymer substrate coating of poly-lysine or poly-ornithine for the cells to adhere and survive. However, polypeptide-based substrates are degraded by proteolysis and it remains a challenge to maintain healthy cell cultures for extended periods of time. Here, we report the development of an enhanced cell culture substrate based on a coating of dendritic polyglycerol amine (dPGA), a no… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…Our work and that of others has previously shown that hiPSC-derived MNs usually coalesce into large cell clusters, which gradually detach from the culture device (Kuijlaars et al, 2016; Taga et al, 2019; Thiry et al, 2020). This situation is most likely due to the degradation of the protein-based substrate (Matrigel or laminin) commonly used for coating, a process that can be mediated by enzymes secreted by the cells (reviewed in Schmidt et al, 2018; Clement et al, submitted). To address this shortcoming, we sought to test the effect of a non-peptide polymer substrate, dPGA, that was shown to improve primary neuron culture conditions, possibly due to its resistance to degradation by cell-secreted proteases (Clement et al, submitted).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our work and that of others has previously shown that hiPSC-derived MNs usually coalesce into large cell clusters, which gradually detach from the culture device (Kuijlaars et al, 2016; Taga et al, 2019; Thiry et al, 2020). This situation is most likely due to the degradation of the protein-based substrate (Matrigel or laminin) commonly used for coating, a process that can be mediated by enzymes secreted by the cells (reviewed in Schmidt et al, 2018; Clement et al, submitted). To address this shortcoming, we sought to test the effect of a non-peptide polymer substrate, dPGA, that was shown to improve primary neuron culture conditions, possibly due to its resistance to degradation by cell-secreted proteases (Clement et al, submitted).…”
Section: Resultsmentioning
confidence: 99%
“…Dendritic polyglycerol amine (dPGA: ∼95 kDa, 50% amine content) (Hellmund et al, 2014; 2015) was synthetized, characterized, and applied to coverslips used for several different neuronal cultures as described in the accompanying manuscript by Clement and colleagues (Clement et al, submitted).…”
Section: Methodsmentioning
confidence: 99%
“…To thoroughly understand whether the specified CAMs have effect on neurite outgrowths, the mean ranks of the samples were compared against PLL, a well-known neuronal coating. 75,76 According to these results, NCAM and N-Cad/NCAM modified samples showed statistically significant differences compared to both PLL adsorbed (Figure 6) and PLL modified surfaces (Supplementary Figure S2). Upon reviewing the literature, it becomes apparent that cell behavior displays significant variability, primarily in response to the concentration or dose-dependent administration of molecules.…”
Section: Neurite Length Measurementsmentioning
confidence: 80%
“…In comparison to the aforementioned findings, our study revealed that the maximum elongation occurred specifically when utilizing NCAM and N‐Cad/NCAM functionalized surfaces. To thoroughly understand whether the specified CAMs have effect on neurite outgrowths, the mean ranks of the samples were compared against PLL, a well‐known neuronal coating 75,76 . According to these results, NCAM and N‐Cad/NCAM modified samples showed statistically significant differences compared to both PLL adsorbed (Figure 6) and PLL modified surfaces (Supplementary Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…Electrophysiological characteristics of iPSC-derived sMNs showed that the PEI-coating condition enabled the capture of increased spontaneous excitability of sMNs derived from sALS iPSC lines, which was consistent with previous ndings in familial ALS iPSC-derived sMN models(Bakkar et al, 2021;Devlin et al, 2015;Perkins et al, 2021;Wainger et al, 2014). Therefore, we recommend PEIcoating for neurodegenerative research.Recently, a new non-peptide polymer, known as dendritic polyglycerol, an amine-based substrate, in combination with Matrigel, was reported to signi cantly improve the long-term culture of iPSC-derived sMNs(Clément et al, 2022;Thiry et al, 2022). This enhanced culture system allowed sustained investigation of various aspects, including cell viability, molecular characteristics, spontaneous network electrophysiological activity, and single-cell RNA sequencing of iPSC-derived mature sMNs for up to two months, where the current study was limited to 7 weeks of culture.…”
mentioning
confidence: 99%